A high-adhesion wear-resistant coating for road roller and preparation method thereof

By using modified polyamide coating on steel wheel rollers, the interaction of 3,4-dihydroxyphenylacetic acid and nano-silicon carbide is used to improve the adhesion and corrosion resistance of the coating, and the wear and corrosion of the steel wheel is solved. Problem, extending the service life of the equipment and reducing pollution to asphalt pavement.

CN119039872BActive Publication Date: 2025-02-07POLY CHANGDA ENGINEERING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411525830.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The steel wheels of the steel wheels of the road roller are prone to wear and corrosion during use, resulting in a degradation of equipment performance and a shortened service life. Rust will pollute the asphalt pavement and affect its performance.

Method used

By using the interaction between 3,4-dihydroxyphenylacetic acid and nano-silicon carbide surface, the grafting rate of active double bond coupling agent is improved, and grafted with 2-(mercaptomethyl)pentanediate is introduced to a large number of active carboxyl groups. , enhance the dispersion and interface bonding of nano silicon carbide in polyamide materials, promote the formation of dense structures, and improve the adhesion, corrosion resistance and mechanical properties of the coating.

Benefits of technology

It significantly improves the adhesion, corrosion resistance and mechanical properties of the coating, extends the service life of the steel wheel, and reduces the pollution of rust on the asphalt pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to a high-adhesion wear-resistant coating for a road roller and a preparation method thereof, and belongs to the technical field of coatings. A preparation method for a high-adhesion wear-resistant coating for a road roller comprises the following steps: after mixing the mixed particles in anhydrous ethanol, adding a coupling agent for constant temperature treatment, centrifuging to obtain solids, washing with alcohol, and placing in an oven for vacuum drying to obtain pretreated composite particles; after mixing the pretreated composite particles and anhydrous ethanol, adding a modified monomer and an initiator, stirring and mixing, and then irradiating with ultraviolet light, filtering and washing with alcohol, placing in an oven for vacuum drying to obtain a prefabricated material; in an inert atmosphere, adding caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid and the prefabricated material to a reactor for constant temperature treatment, adding an auxiliary agent for blending, and obtaining the coating. The coating prepared by the present invention has excellent adhesion, corrosion resistance and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings and relates to a high-adhesion wear-resistant coating for a road roller and a preparation method thereof. Background Art

[0002] As an important road construction equipment, the performance and service life of steel wheel rollers directly affect the quality of the project and the progress of the construction. During the use of steel wheel rollers, the steel wheels are in contact with the road surface for a long time and are subjected to high load pressure, which is prone to wear, corrosion and other problems. Rust not only affects the appearance of the steel wheel of the roller, but also pollutes the asphalt pavement during the rolling process, affecting the performance of the asphalt pavement. Therefore, rust removal of the steel wheel of the roller is a key link to ensure the normal operation of the roller and extend its service life. How to effectively improve the wear resistance and corrosion resistance of the steel wheel is an urgent problem to be solved in the current construction machinery industry.

[0003] As a high-performance anti-corrosion coating, polyamide coating can effectively prevent corrosion on metal surfaces. Its main component, polyamide resin, has good chemical resistance and heat resistance. It is not only suitable for the anti-corrosion treatment of large metal structures such as industrial equipment, pipelines, and storage tanks, but also for the surface protection of metal components such as automobiles, ships, and bridges. By spraying, brushing, or dipping, polyamide coating can be evenly covered on the metal surface to form a solid protective layer, thereby effectively extending the service life of the metal material and effectively isolating the metal from contact with external corrosive substances. In addition, polyamide coating also has good mechanical properties and weather resistance, and can maintain its anti-corrosion effect for a long time in harsh environments.

[0004] As an advanced nanomaterial, nano silicon carbide plays an important role in polyamide coatings, especially in improving corrosion resistance and wear resistance. Specifically, the addition of nano silicon carbide can effectively fill the tiny defects and pores in polyamide coatings, thereby reducing the penetration path of corrosive media and improving the density of the coating. In this way, the corrosion resistance of the coating has been significantly improved, and the substrate can be better protected from corrosive environments such as salt spray, acid rain, and chemicals. In addition, the high hardness of nano silicon carbide also gives polyamide coatings excellent wear resistance, allowing it to maintain surface integrity under conditions of mechanical wear and friction. However, due to the high activity of nano silicon carbide and the chemical properties of polyamide resin, specific surface treatment technology is required to improve the compatibility between nano silicon carbide particles and the polyamide matrix. Summary of the invention

[0005] The purpose of the present invention is to provide a high-adhesion wear-resistant coating for a road roller and a preparation method thereof. The present invention utilizes the interaction between 3,4-dihydroxyphenylacetic acid and the surface of nano-silicon carbide to improve the grafting rate of the active double bond coupling agent, grafts with 2-(mercaptomethyl)pentane dioic acid, introduces a large number of active carboxyl groups, enhances the dispersibility and interfacial bonding force of nano-silicon carbide in polyamide materials, promotes the formation of a dense structure, and improves the adhesion, corrosion resistance and mechanical properties of the coating.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A method for preparing a high-adhesion wear-resistant coating for a road roller comprises the following steps:

[0008] 1) The mixed particles are placed in anhydrous ethanol and mixed, a coupling agent is added and the mixture is treated at a constant temperature, solids are taken out by centrifugation, washed with alcohol, and dried in a vacuum oven to obtain pretreated composite particles;

[0009] 2) After the pretreated composite particles and anhydrous ethanol are mixed, the modified monomer and the initiator are added, stirred and mixed, and then ultraviolet irradiation treatment is performed, and then the mixture is filtered and washed with alcohol, and then placed in an oven for vacuum drying to obtain a prefabricated material;

[0010] 3) Under an inert atmosphere, caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid and prefabricated materials are added into a reaction kettle for constant temperature treatment, and then an auxiliary agent is added and blended to obtain the product.

[0011] As a preferred technical solution of the present invention, in step 1), the constant temperature treatment is stirring at 50-60°C and 200-400 r / min for 5-6 hours; the alcohol washing is washing three times with anhydrous ethanol; and the vacuum drying is vacuum drying at 80°C for 6-8 hours.

[0012] As a preferred technical solution of the present invention, in step 1), the mass ratio of the mixed particles, anhydrous ethanol and coupling agent is 10-12:40-50:2.4-2.8; the coupling agent is silane coupling agent A171.

[0013] As a preferred technical solution of the present invention, in step 1), the preparation of the mixed particles includes grinding nano-silicon carbide and 3,4-dihydroxyphenylacetic acid in a 70wt% ethanol solution for 30-40min, and drying; the mass ratio of the nano-silicon carbide, 3,4-dihydroxyphenylacetic acid and ethanol solution is 3.2-3.4:0.3-0.4:20.

[0014] As a preferred technical solution of the present invention, in step 2), the stirring and mixing is stirring at a speed of 400-600 r / min for 10-15 min; the ultraviolet irradiation treatment is ultraviolet irradiation at a wavelength of 365 nm for 6-8 h; the alcohol washing is washing with anhydrous ethanol three times; and the vacuum drying is vacuum drying at a temperature of 80°C to constant weight.

[0015] As a preferred technical solution of the present invention, in step 2), the modified monomer is 2-(mercaptomethyl)pentane dioic acid; the initiator is photoinitiator 1173; the mass ratio of the pretreated composite particles, anhydrous ethanol, modified monomer and initiator is 8-10:38-42:2.2-2.5:0.06-0.08.

[0016] As a preferred technical solution of the present invention, in step 3), the inert atmosphere is a nitrogen atmosphere; the constant temperature treatment is stirring at a temperature of 250-260° C. and a speed of 400-500 r / min for 8-10 hours.

[0017] As a preferred technical solution of the present invention, in step 3), the mass ratio of caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid, prefabricated material and auxiliary agent is 20-22: 5-6: 6.0-6.4: 1.0-1.2: 4.8-5.2: 0.8-1.0; the auxiliary agent is one or more of an antioxidant, a leveling agent, an inorganic antibacterial agent and a pigment.

[0018] As a preferred technical solution of the present invention, in step 3), the auxiliary agent is prepared by mixing antioxidant 1010 and titanium dioxide in a mass ratio of 1.3:1.

[0019] Beneficial effects of the present invention:

[0020] The invention utilizes the interaction between 3,4-dihydroxyphenylacetic acid and the surface of nano silicon carbide to improve the grafting rate of active double bond coupling agent, grafts with 2-(mercaptomethyl)pentane dioic acid, introduces a large number of active carboxyl groups, enhances the dispersibility and interface bonding force of nano silicon carbide in polyamide materials, promotes the formation of dense structure, and improves the adhesion, corrosion resistance and mechanical properties of coatings. DETAILED DESCRIPTION

[0021] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0022] Example 1

[0023] A method for preparing a high-adhesion wear-resistant coating for a road roller comprises the following steps:

[0024] 1) After the mixed particles are placed in anhydrous ethanol and mixed, a coupling agent is added, stirred at 50°C and 200 r / min for 5 hours, the solid is centrifuged, washed three times with anhydrous ethanol, placed in an oven, and vacuum dried at 80°C for 6 hours to obtain pretreated composite particles; the mass ratio of the mixed particles, anhydrous ethanol and the coupling agent is 10:40:2.4; the coupling agent is silane coupling agent A171; the preparation of the mixed particles includes grinding nano-silicon carbide and 3,4-dihydroxyphenylacetic acid in a 70wt% ethanol solution for 30 minutes, and drying; the mass ratio of the nano-silicon carbide, 3,4-dihydroxyphenylacetic acid and ethanol solution is 3.2:0.3:20;

[0025] 2) After the pretreated composite particles and anhydrous ethanol are mixed, the modified monomer and the initiator are added and stirred at a speed of 400 r / min for 10 minutes, and then irradiated with ultraviolet light at a wavelength of 365 nm for 6 hours. After filtration, the mixture is washed three times with anhydrous ethanol, placed in an oven, and vacuum dried at a temperature of 80° C. to constant weight to obtain a prefabricated material; the mass ratio of the pretreated composite particles, anhydrous ethanol, the modified monomer and the initiator is 8:38:2.2:0.06; the modified monomer is 2-(mercaptomethyl)pentane dioic acid; and the initiator is photoinitiator 1173;

[0026] 3) Under a nitrogen atmosphere, caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid and a prefabricated material are added into a reactor, stirred at 250°C and 400 r / min for 8 hours, and then an auxiliary agent is added and blended to obtain the product; wherein the mass ratio of the caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid, the prefabricated material and the auxiliary agent is 20:5:6.0:1.0:4.8:0.8; and the auxiliary agent is prepared by mixing antioxidant 1010 and titanium dioxide in a mass ratio of 1.3:1.

[0027] Example 2

[0028] A method for preparing a high-adhesion wear-resistant coating for a road roller comprises the following steps:

[0029] 1) After the mixed particles are placed in anhydrous ethanol and mixed, a coupling agent is added and stirred at 53°C and 260r / min for 5.5h, the solid is centrifuged, washed three times with anhydrous ethanol, placed in an oven, and vacuum dried at 80°C for 6.5h to obtain pretreated composite particles; the mass ratio of the mixed particles, anhydrous ethanol and the coupling agent is 10.7:43:2.5; the coupling agent is silane coupling agent A171; the preparation of the mixed particles includes grinding nano-silicon carbide and 3,4-dihydroxyphenylacetic acid in a 70wt% ethanol solution for 35min, and drying; the mass ratio of the nano-silicon carbide, 3,4-dihydroxyphenylacetic acid and ethanol solution is 3.27:0.33:20;

[0030] 2) After the pretreated composite particles and anhydrous ethanol are mixed, the modified monomer and the initiator are added and stirred at a speed of 460 r / min for 12 minutes, and then irradiated with ultraviolet light at a wavelength of 365 nm for 6.5 hours. After filtration, the mixture is washed three times with anhydrous ethanol, placed in an oven, and vacuum dried at a temperature of 80° C. to constant weight to obtain a prefabricated material; the mass ratio of the pretreated composite particles, anhydrous ethanol, the modified monomer and the initiator is 8.7:39:2.3:0.07; the modified monomer is 2-(mercaptomethyl)pentane dioic acid; and the initiator is photoinitiator 1173;

[0031] 3) Under a nitrogen atmosphere, caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid and a prefabricated material are added into a reactor, stirred at 255°C and 430 r / min for 8.5 h, and then an auxiliary agent is added and blended to obtain a product; wherein the mass ratio of the caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid, the prefabricated material and the auxiliary agent is 20.7:5.3:6.1:1.1:4.9:0.9; and the auxiliary agent is prepared by mixing antioxidant 1010 and titanium dioxide in a mass ratio of 1.3:1.

[0032] Example 3

[0033] A method for preparing a high-adhesion wear-resistant coating for a road roller comprises the following steps:

[0034] 1) After the mixed particles are placed in anhydrous ethanol and mixed, a coupling agent is added and stirred at 57°C and 330 r / min for 5.5 hours, the solid is centrifuged, washed three times with anhydrous ethanol, placed in an oven, and vacuum dried at 80°C for 7.5 hours to obtain pretreated composite particles; the mass ratio of the mixed particles, anhydrous ethanol and the coupling agent is 11.3:47:2.7; the coupling agent is silane coupling agent A171; the preparation of the mixed particles includes grinding nano-silicon carbide and 3,4-dihydroxyphenylacetic acid in a 70wt% ethanol solution for 35 minutes and drying; the mass ratio of the nano-silicon carbide, 3,4-dihydroxyphenylacetic acid and ethanol solution is 3.3:0.37:20;

[0035] 2) After the pretreated composite particles and anhydrous ethanol are mixed, the modified monomer and the initiator are added and stirred at a speed of 533 r / min for 13 minutes, and then irradiated with ultraviolet light at a wavelength of 365 nm for 7.3 hours. After filtration, the mixture is washed three times with anhydrous ethanol, placed in an oven, and vacuum dried at a temperature of 80° C. to constant weight to obtain a prefabricated material; the mass ratio of the pretreated composite particles, anhydrous ethanol, the modified monomer and the initiator is 9.3:41:2.4:0.07; the modified monomer is 2-(mercaptomethyl)pentane dioic acid; and the initiator is photoinitiator 1173;

[0036] 3) Under a nitrogen atmosphere, caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid and a prefabricated material are added into a reactor, stirred at 257°C and 467 r / min for 9.3 h, and then an auxiliary agent is added and blended to obtain the product; wherein the mass ratio of the caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid, the prefabricated material and the auxiliary agent is 21.3:5.7:6.3:1.1:5.1:0.9; and the auxiliary agent is prepared by mixing antioxidant 1010 and titanium dioxide in a mass ratio of 1.3:1.

[0037] Example 4

[0038] A method for preparing a high-adhesion wear-resistant coating for a road roller comprises the following steps:

[0039] 1) After the mixed particles are placed in anhydrous ethanol and mixed, a coupling agent is added, stirred at 60°C and 400r / min for 6h, the solid is centrifuged, washed three times with anhydrous ethanol, placed in an oven, and vacuum dried at 80°C for 8h to obtain pretreated composite particles; the mass ratio of the mixed particles, anhydrous ethanol and the coupling agent is 12:50:2.8; the coupling agent is silane coupling agent A171; the preparation of the mixed particles includes grinding nano-silicon carbide and 3,4-dihydroxyphenylacetic acid in a 70wt% ethanol solution for 40min, and drying; the mass ratio of the nano-silicon carbide, 3,4-dihydroxyphenylacetic acid and ethanol solution is 3.4:0.4:20;

[0040] 2) After the pretreated composite particles and anhydrous ethanol are mixed, the modified monomer and the initiator are added and stirred at a speed of 600 r / min for 15 minutes, and then irradiated with ultraviolet light at a wavelength of 365 nm for 8 hours. After filtration, the mixture is washed three times with anhydrous ethanol, placed in an oven, and vacuum dried at a temperature of 80° C. to constant weight to obtain a prefabricated material; the mass ratio of the pretreated composite particles, anhydrous ethanol, the modified monomer and the initiator is 10:42:2.5:0.08; the modified monomer is 2-(mercaptomethyl)pentane dioic acid; and the initiator is photoinitiator 1173;

[0041] 3) Under a nitrogen atmosphere, caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid and a prefabricated material are added into a reactor, stirred at 260°C and 500 r / min for 10 hours, and then an auxiliary agent is added and blended to obtain the product; wherein the mass ratio of the caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid, the prefabricated material and the auxiliary agent is 22:6:6.4:1.2:5.2:1.0; and the auxiliary agent is prepared by mixing antioxidant 1010 and titanium dioxide in a mass ratio of 1.3:1.

[0042] Comparative Example 1

[0043] Compared with Example 4, Comparative Example 1 is different in that nano-silicon carbide is used instead of the mixed particles in step 1), and the other components, preparation steps and parameters are the same.

[0044] Comparative Example 2

[0045] Compared with Example 4, Comparative Example 2 is different in that 3,5-dihydroxyphenylacetic acid is used instead of 3,4-dihydroxyphenylacetic acid, and the other components, preparation steps and parameters are the same.

[0046] Comparative Example 3

[0047] Compared with Example 4, Comparative Example 3 is different in that no coupling agent is used in step 1), and the other components, preparation steps and parameters are the same.

[0048] Comparative Example 4

[0049] Compared with Example 4, Comparative Example 4 is different in that 2-(mercaptomethyl)pentanedioic acid is not used, and the other components, preparation steps and parameters are the same.

[0050] Comparative Example 5

[0051] Compared with Example 4, Comparative Example 5 is different in that nano-silicon carbide is used to replace the prefabricated material in step 3), and the other components, preparation steps and parameters are the same.

[0052] The coatings prepared in Examples 1-4 and Comparative Examples 1-5 were subjected to the following performance tests, respectively. The test results are shown in Table 1.

[0053] Hardness test: GB / T 6739-2006;

[0054] Adhesion test: According to GB / T 5210-2006;

[0055] Salt spray resistance test: according to GB / T1771 1991;

[0056] Table 1

[0057]

[0058] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-5, the coatings prepared in Examples 1-4 of the present invention have excellent hardness and corrosion resistance, good adhesion and certain wear resistance.

[0059] From the comparison of Examples 1-4 with Comparative Examples 1-5, combined with the comparative analysis of Table 1, it can be seen that this is because the present invention interacts with the surface of nano-silicon carbide through the hydroxyl and carboxyl functional groups of 3,4-dihydroxyphenylacetic acid to change the surface energy and charge distribution of the nanoparticles, thereby suppressing the self-agglomeration of nano-silicon carbide and effectively improving the grafting rate of the coupling agent, introducing an unsaturated double bond with high reactivity, and then using the double bond to react with the thiol group of 2-(mercaptomethyl)pentane dioic acid under ultraviolet irradiation to introduce a large number of active carboxyl groups, thereby improving the nanoparticles. While improving the dispersibility and interfacial bonding strength of silicon carbide, the carboxyl group can participate in the reaction of polyamide materials, so that nano silicon carbide is distributed in the polyamide material system by chemical bonding, which improves the adhesion of the coating. At the same time, multiple carboxyl groups can effectively promote the formation of a dense structure, which is beneficial to improving the corrosion resistance and mechanical properties of the material; in addition, by containing N, O, S element compounds and catechol structures at the same time, it can form an adsorption-type protective layer on the metal surface through physical adsorption with the metal, slowing down the corrosion of the metal surface by environmental factors, and significantly improving its corrosion resistance.

[0060] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-adhesion wear-resistant coating for a road roller, characterized in that: The preparation method comprises the following steps: 1) After the mixed particles are placed in anhydrous ethanol and mixed, a coupling agent is added and the mixture is treated at a constant temperature, solids are centrifuged, washed with alcohol, and placed in an oven for vacuum drying to obtain pretreated composite particles; the mass ratio of the mixed particles, anhydrous ethanol and the coupling agent is 10-12:40-50:2.4-2.8; the coupling agent is silane coupling agent A171; the preparation of the mixed particles comprises placing nano-silicon carbide and 3,4-dihydroxyphenylacetic acid in a 70wt% ethanol solution, grinding for 30-40min, and drying; 2) After the pretreated composite particles and anhydrous ethanol are mixed, the modified monomer and the initiator are added, stirred and mixed, and then ultraviolet irradiation treatment is performed, and then the prefabricated material is obtained after alcohol washing after suction filtration and vacuum drying in an oven; the mass ratio of the pretreated composite particles, anhydrous ethanol, the modified monomer and the initiator is 8-10:38-42:2.2-2.5:0.06-0.08; the modified monomer is 2-(mercaptomethyl)pentane dioic acid; 3) Under an inert atmosphere, caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid and a prefabricated material are added to a reaction kettle for constant temperature treatment, and then an auxiliary agent is added and blended to obtain the product; the mass ratio of the caprolactam, hexamethylenediamine, terephthalic acid, aminocaproic acid, the prefabricated material and the auxiliary agent is 20-22: 5-6: 6.0-6.4: 1.0-1.2: 4.8-5.2: 0.8-1.

0.

2. The method for preparing a high-adhesion wear-resistant coating for a road roller according to claim 1, characterized in that: In step 1), the constant temperature treatment is stirring at a temperature of 50-60° C. and a speed of 200-400 r / min for 5-6 hours.

3. The method for preparing a high adhesion wear-resistant coating for a road roller according to claim 1, characterized in that: In step 1), the alcohol washing is washing with anhydrous ethanol three times; and the vacuum drying is vacuum drying at a temperature of 80° C. for 6-8 hours.

4. The method for preparing a high adhesion wear-resistant coating for a road roller according to claim 1, characterized in that: In step 1), the mass ratio of the nano-silicon carbide, 3,4-dihydroxyphenylacetic acid and ethanol solution is 3.2-3.4:0.3-0.4:

20.

5. The method for preparing a high-adhesion wear-resistant coating for a road roller according to claim 1, characterized in that: In step 2), the ultraviolet irradiation treatment is ultraviolet irradiation at a wavelength of 365nm for 6-8h.

6. The method for preparing a high-adhesion wear-resistant coating for a road roller according to claim 1, characterized in that: In step 2), the stirring and mixing is stirring at a speed of 400-600 r / min for 10-15 min; the alcohol washing is washing with anhydrous ethanol three times; and the vacuum drying is vacuum drying at a temperature of 80° C. to constant weight.

7. The method for preparing a high adhesion wear-resistant coating for a road roller according to claim 1, characterized in that: In step 2), the initiator is a photoinitiator.

8. The method for preparing a high-adhesion wear-resistant coating for a road roller according to claim 1, characterized in that: In step 3), the inert atmosphere is a nitrogen atmosphere; the constant temperature treatment is stirring at a temperature of 250-260° C. and a speed of 400-500 r / min for 8-10 hours.

9. The method for preparing a high-adhesion wear-resistant coating for a road roller according to claim 1, characterized in that: In step 3), the auxiliary agent is one or more of an antioxidant, a leveling agent, an inorganic antibacterial agent and a pigment.

10. A high adhesion wear-resistant coating for a road roller prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of MC nylon / SiC @ SiO2 composite material

    CN111961337A

  • Wear-resistant graphite paint for automobile windscreen wiper and preparation method of wear-resistant graphite paint

    CN115160886A